Comparative evaluation of isoflurane and sevoflurane for maintenance of anaesthesia in buffaloes undergoing diaphragmatic herniorrhaphy - CHAUDHARY, R N; TAYAL, RISHI; BEHL, S M; KUMAR, ASHOK; SHARMA, SATBIR (The Indian Journal of Animal Sciences, 2017)
The study was conducted in 12 adult female buffaloes suffering from diaphragmatic hernia (DH). The animals were randomly divided in 2 groups of 6 each. DH was repaired under general anaesthesia using glycopyrrholatexylazine-butorphanol-thiopentone maintained with isoflurane and sevoflurane in group TI and TS, respectively. Clinical and behavioural parameters were observed during herniorrhaphy while physiological, haematological and biochemical parameters were recorded at different intervals (before rumenotomy, before premedication, 5 min after thiopentone injection, at 15 min and 30 min of inhalant anaesthesia, at recovery and at 24 h of recovery). No significant difference was seen in sedation, muscle relaxation and analgesia scores between the groups. The respiratory rate was less depressed and corneal reflex was mostly intact during maintenance in TS group. Recovery and standing with ataxia in TS group was significantly earlier than TI group. There was no significant difference in haematological and blood biochemical parameters between the groups. The results indicated that sevoflurane is a better maintenance agent than isoflurane for maintenance of general anaesthesia in buffaloes undergoing DH.